Observation of critical scaling in spin glasses below Tc using thermoremanent magnetization - Kenning, G. G.; Brandt, M.; Brake, R.; Hepler, M.; Tennant, D. (Frontiers in Physics, 2024)
Time-dependent Thermoremanent Magnetization (TRM) studies have been instrumental in probing energy dynamics within the spin glass phase. In this paper, we will review the evolution of the TRM experiment over the last half century and discuss some aspects related to how it has been employed in the understanding of spin glasses. We will also report on recent experiments using high resolution DC SQUID magnetometry to probe the TRM at temperatures less than but near to the transition temperature T c . These experiments have been performed as a function of waiting time, temperature, and five different magnetic fields. We find that as the transition temperature is approached from below, the characteristic time scale of the TRM is suppressed up to several orders of magnitude in time. In the highest temperature region, we find that the waiting time effect goes away, and a waiting time independent crossover line is reached. We also find that increasing the magnetic field, further suppresses the crossover line. Using a first principles energy argument across the crossover line, we derive an equation that is an excellent fit to the crossover lines for all magnetic fields probed. The data show strong evidence for critical slowing down and an H = 0 Oe phase transition.